Being an historian: an investigation into the impact of using online source banks to replicate the research experience of historians in the A-level classroom - Conway, R (2019)
This study investigated ways to improve students’ understanding of and engagement with contemporary sources in the history classroom. The study followed an action research model working with two teachers to support A-level history students in completing three different historical enquiries using online source archives, analysing the impact and adapting the structure of the activity each time. The lessons were delivered to a class of year 12 historians consisting of 12 students.